Strategi Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Dalam Meningkatkan Investasi di Provinsi Sumatera Utara - Adriansyah Hidayat; Muhammad Yafiz (Journal of Islamic Economics and Finance, 2023)
Investment is a benchmark for whether a country can be said to have a good or low level of economic growth. The rate of investment affects the level of state welfare because investment encourages the state to create production to fulfill state affairs and the nation's welfare. Investment policy also has a positive role in reducing poverty and unemployment, because economic growth depends on high savings and investment. If savings and investment are low then the economic growth of society and the country will also be low. To achieve the goal of realizing the vision and mission or objectives of the One Stop Integrated Investment and Services Agency (DPMPTSP) itself, an appropriate promotional strategic work plan is needed to be considered by the regional government, so that investment in North Sumatra increases. Various activities have not had a significant impact in increasing investment, the increase in promotional activities carried out is not in line with the increase in investment value. The research technique used in this research can be a subjective expressive qualitative strategy, in the form of specific information in terms of words that match the characteristics subjective approach. Qualitative is collecting important and additional information through perception, interviews and documentation. The results of this research show that the North Sumatra Provincial Government has implemented an investment strategy, improved the quality and skills of the community through training, and carried out comprehensive investment promotion activities (such as holding seminars and investment forum meetings) at home and abroad. Accelerate infrastructure development and support regional investment development. Distribution of Capital Investment; Focus on Food, Infrastructure and Energy Development; Environmentally sound investment (green investment) Empowerment of Micro, Small and Medium Enterprises and Cooperatives (UMKMK); Providing facilities, convenience and investment incentives; and Investment Promotion. A conducive and competitive investment climate.